Monitoring Spruce Budworm with Light Traps: The Effect of Trap Position - Marc Rhainds; Edward G. Kettela (Psyche: A Journal of Entomology)
Daily records of adult spruce budworms, Choristoneura fumiferana (Clemens) (Lepidoptera: Tortricidae), captured at light traps at multiple locations in New Brunswick in the 1970s, are analyzed in relation to the physical position of light traps (tree canopies or forest clearings). Captures at light traps deployed in tree canopies were 4–400 times greater than those in forest clearings, especially for males. The phenology of captures (median date or duration of flight period) did not differ in relation to trap location. Captures of both males and females in tree canopies were highly correlated with egg densities, whereas no significant relationship was observed for either sex in forest clearings. Monitoring programs for spruce budworm adults using light traps should be standardized by deploying traps in tree canopies.